A short and efficient stereoselective synthesis of the potent 5-lipoxygenase inhibitor, CMI-977 - Dixon, D; Ley, S; Reynolds, D; Chorghade, MS (2001)
A short and efficient synthesis of the potent 5-lipoxygenase inhibitor CMI-977 is described using as the key step a stereoselective anomeric oxygen to carbon rearrangement of an alkynyl stannane tetrahydrofuranyl ether derivative mediated by boron trifluoride etherate.